Prognostic and clinicopathological value of GATA binding protein 3 in breast cancer: A systematic review and meta-analysis. - Yawen Guo; Pan Yu; Zeming Liu; Yusufu Maimaiti; Chen Chen; Yunke Zhang; Xingjie Yin; Shan Wang; Chunping Liu; Tao Huang (PLoS ONE, 2017)
The potential prognostic value of GATA binding protein 3 (GATA3) in breast cancer has recently increased, although the evidence is inconclusive. This meta-analysis of 10 articles involving 5,080 breast cancer patients explored the prognostic and clinicopathological value of GATA3 in breast cancer. Time to tumor progression (TTP) and overall survival (OS) were primary endpoints. Pooled hazard ratio (HR), pooled risk ratio (RR), and 95% confidence interval (CI) were calculated to evaluate the association between GATA3, prognosis, and clinicopathological parameters. High GATA3 expression predicts breast cancer, with a HR (HR = 0.671; 95% CI = 0.475-0.947; P = 0.023) of TTP, but is not associated with OS (HR = 0.889; 95% CI = 0.789-1.001; P = 0.052). GATA3 overexpression is associated with positive ER (RR = 3.155; 95% CI = 1.680-5.923; P = 0.000), positive PR (RR = 3.949; 95% CI = 1.567-9.954, P = 0.004), lower nuclear grade (RR = 0.435; 95% CI = 0.369-0.514; P = 0.000), and smaller tumor size (RR = 0.816; 95% CI = 0.709-0.940; P = 0.005). High GATA3 expression may predict TTP in breast cancer, and such patients may show better clinicopathological features.